The Role of Law in National Economic Development through Partnerships in Facing the Global Era for Improving Community Welfare - Siregar, Hamdan Azhar; Untoro, Untoro; Siregar, Ahmad Munawir (AMCA Journal of Community Development, 2025)
Economic liberalization is currently the lifeblood of the global economy. Conceptually, a market that can run perfectly is the most ideal way to achieve normative goals, namely, the prosperity of the people as envisioned. This pact is very interesting to study considering how the role of partnerships in building the economy, and how the role of law in development provides prosperity for the community. This research uses normative juridical research, with the nature of descriptive analysis research, while data collection techniques are through library studies or document studies, but field data is also used to support and complement library data. After the data is collected, it is analysed in a qualitative juridical way. In Indonesia, there are three economic actors: Cooperatives, BUMN and Private. The law must play a role in building togetherness or partnership among the three economic actors; the rules need to provide direction to economic actors. This is where the law is expected to really play a role in eliminating these differences through partnerships. This partnership is important to build cooperation, because cooperatives, BUMN and Private are three economic actors who live in the community. The goal that must be achieved by the partnership is to provide access to sources of capital, technology and information, as well as to the marketing of the products of its members, and to foster the power of its human capabilities and to overcome management and organisation. This is needed in connection with the threats to the world economy in the era of globalization, as well as opportunities.